2000
DOI: 10.1016/s0893-133x(99)00139-6
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Hydroxylase- and Dopamine Transporter-Immunoreactive Axons in the Primate Cerebellum Evidence for a Lobular- and Laminar-Specific Dopamine Innervation

Abstract: The cerebellum seems to play a critical role in many motor and cognitive functions, including those that are disturbed in schizophrenia. Although dopamine is known to influence the motor or cognitive functions mediated by other brain regions and to play a role in the pathophysiologyThe primary function of the cerebellum has traditionally been considered to involve the control and integration of motor processes, including the coordination of goal-directed movements and the regulation of posture (Ito 1984). Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
112
3
3

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(127 citation statements)
references
References 55 publications
9
112
3
3
Order By: Relevance
“…Therefore, the observed effect of MPH may reflect MPH effects on cerebellar noradrenergic systems, although we cannot rule out contributions owing to effects of MPH on serotonergic systems. The dopaminergic innervation of the human cerebellar vermis is variably described as being sparse to rich (see Melchitzsky and Lewis, 2000), although Volkow et al (2001) have shown using PET and [ 11 C]raclopride that MPH does not appear to increase cerebellar dopamine levels. Therefore, it is uncertain whether the effects of MPH on rCBF in the cerebellar vermis are related to effects on dopaminergic systems.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the observed effect of MPH may reflect MPH effects on cerebellar noradrenergic systems, although we cannot rule out contributions owing to effects of MPH on serotonergic systems. The dopaminergic innervation of the human cerebellar vermis is variably described as being sparse to rich (see Melchitzsky and Lewis, 2000), although Volkow et al (2001) have shown using PET and [ 11 C]raclopride that MPH does not appear to increase cerebellar dopamine levels. Therefore, it is uncertain whether the effects of MPH on rCBF in the cerebellar vermis are related to effects on dopaminergic systems.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported cerebellar midline (vermis) activation by alcohol odor cues and by stimulant expectancy (Schneider et al, 2001;Volkow et al, 2003). Such findings are intriguing in light of reports localizing DAT immunoreactivity (DAT-IR) and mRNA in primate cerebellar vermis (Melchitzky and Lewis, 2000;Hurley et al, 2003). Moreover, in rodents, the vermis is a context-dependent self-stimulation site (Ball et al, 1974) and vermis lesions alter cortical dopamine turnover (Snider and Snider, 1977).…”
Section: Introductionmentioning
confidence: 94%
“…Relative regional [ 11 C]altropane accumulation levels were calculated over the first 6 min after ligand infusion as quotients of summed activity within each ROI, divided by PSV summed activity. The referent PSV reportedly is DAT-IR devoid (Melchitzky and Lewis, 2000). For regions with bilateral representations, ROI values were averaged across hemispheres.…”
Section: Bold Fmrimentioning
confidence: 99%
See 2 more Smart Citations